Analisis Manajemen Konflik dalam Penyelesaian Masalah Organisasi di PTPN IV Regional III Palmco Kebun Terantam (Studi Kasus: Pekerja Pemanen Sawit) - Riska Febrianti Aulia; Muhammad Syukri Albani Nasution; Imsar (STIE Indonesia Banking School, 2025)
This research aims to analyze conflict management strategies implemented at PTPN IV Terantam Plantation in handling organizational conflicts, specifically those involving oil palm harvesters. Using a qualitative approach with a case study design, this research identifies types of conflicts, their causes, and their impact on productivity and working relationships. The subjects of this research consist of three main groups: management, supervisors, and harvesters. Data collection methods include direct observation, in-depth interviews, and documentation. Data analysis in this research is conducted through three main stages: data reduction, data presentation, and verification or conclusion drawing. The research results show that conflicts most often occur due to miscommunication between management and workers, workers' unawareness of their rights, and interpersonal tension among workers. The conflict management strategies used include an integrative conflict management approach through improved two-way communication, ongoing education, and a participatory clarification forum. This strategy has proven effective in building trust, increasing work motivation, and creating a conducive work environment.